Asymmetric Flow-Performance Relationship: Case of Chinese Equity Funds - Rao, Zia-ur-Rehman; Tauni, Muhammad Zubair; Rehman, Ajid ur (International Journal of Economics and Financial Issues, 2016)
We investigate the relationship of fund flow and fund performance by using the sample of 557 Chinese equity mutual funds for the period of 11 years. We apply fund fixed effect regression model on unbalanced panel data and find that relationship between fund flow and fund performance is positive. Like previous studies, our findings also exhibit the asymmetric flow-performance relationship which implies that investors' response is more sensitive to good past performance as compared to bad past performance. Furthermore, size and age of fund weaken the flow-performance relationship. Keywords: Fund Flow, Mutual funds, China, Flow-Performance Relationship JEL Classifications: G23, L14